A new species of Physiculus (Teleostei: Moridae) from the Cape Verde Islands (Eastern Central Atlantic) - González, José A.; Triay-Portella, Raül; Biscoito, Manuel (Zootaxa, 2018)
A new species of Physiculus, P. caboverdensis n. sp., is described from the outer shelf and upper slope of the Cape Verde Islands. This species differs from all other congeners from the Atlantic Ocean by its peculiar dentition, composed of large fang-like teeth in both jaws, interspaced with smaller canine-like teeth, arranged in two series on upper jaw and one on lower. This is the tenth species of the genus to occur in the Atlantic Ocean and the third to be recorded from the Cape Verde Islands.